2017
DOI: 10.1007/s40097-017-0248-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and comparative studies of MnFe2O4 nanoparticles with different natural polymers by sol–gel method: structural, morphological, optical, magnetic, catalytic and biological activities

Abstract: Nanosized manganese ferrite (MnFe 2 O 4 ) particles were prepared by sol-gel method using natural polymers like wheat flour (WF) and potato flour (PF) as surfactants and its structural, morphological, optical and magnetic characteristics were studied by X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FT-IR), scanning electron microscope (SEM), photoluminescence spectroscopy (PL) and vibration sample magnetometer (VSM). Brunauer-Emmett-Teller (BET) surface area test also performed and the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(16 citation statements)
references
References 42 publications
2
13
0
1
Order By: Relevance
“…It is evident from Figure 4a that the FTIR bands are found at 449, 502, 572, 702, 871, 1004, 1409, 1483, 2164, and 3745 cm −1 . [ 50–59 ] In the spinel structure, cations reside in octahedral and tetrahedral sites depending upon their octahedral site preference energy with different cationic stretching vibrations. [ 52–54,57,58 ]…”
Section: Resultsmentioning
confidence: 99%
“…It is evident from Figure 4a that the FTIR bands are found at 449, 502, 572, 702, 871, 1004, 1409, 1483, 2164, and 3745 cm −1 . [ 50–59 ] In the spinel structure, cations reside in octahedral and tetrahedral sites depending upon their octahedral site preference energy with different cationic stretching vibrations. [ 52–54,57,58 ]…”
Section: Resultsmentioning
confidence: 99%
“…The inset shows d-spacing of 0.49 nm, consistent with the (111) plane of the Mn crystal structure. EDAX analysis from HRTEM represents the presence of Mn, Fe and O elements in figure 2(d) and the compositional analysis (table 1) represents the weight and atomic % of element distribution in the system [25,26]. From which, it is found that the Fe to Mn ratio was 2.16:1 that is close to the stoichiometry of theoretical ratio.…”
Section: Resultsmentioning
confidence: 56%
“…Nanopartikel superparamagnetik ferrit memiliki aktivitas antibakteri yang potensial (Jacintha et al 2017). Penelitian sebelumnya telah melaporkan nanopartikel MnFe2O4 PEG-chitosan yang disintesis menggunakan ekstrak Carum copticum memiliki aktivitas antibakteri yang signifikan terutama terhadap bakteri gram negatif (Esmaeili & Ghobadanpuour 2016).…”
Section: Pendahuluanunclassified